A performance of the Malaysia rugby sevens team based on selected performance indicators on a various Asia-level rugby sevens tournament from 2018 – 2020 / Norasrudin Sulaiman, Hasbullah Ismail, Hosni bin Hasan and Raja Mohamad Firhad Raja Azidin - Sulaiman, Norasrudin; Ismail, Hasbullah; Hasan, Hosni; Raja Azidin, Raja Mohammed Firhad (Universiti Teknologi MARA, 2023)
Identification of performance indicators related to the status of the game (winning and losing) is needed for a tactical approach especially in improving the Malaysia Men’s Rugby Seven team. This study aims to characterize team performance indicators based on the game status of Malaysia men’s rugby sevens teams. A total of 16 matches (winning, n=8, losing, n=8) for the national team from various Asia-level tournaments from years 2018 to 2020 were collected using Sportscode performance analysis software and a notational analysis form. The performance indicators variables are extracted from the excel spreadsheet using the visual basic application of Microsoft excel before being exported to SPSS version 26 with the significant value is set at p<0.05. Based on the analysis, there is no significant difference in the winning performance and losing performance of the Malaysia Men’s Rugby Sevens Team.